Lexical verbs in verb-noun collocations : empirical evidence from a Malay ESL learner corpus - Shazila Abdullah,; Roslina Abdul Aziz,; Rafidah Kamaruddin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Previous studies have shown that verbs are indeed one of the essential lexical items that seem to dominate a text. At tertiary levels, learners are often presented with a list of verbs that are essential for English for Academic Purposes (EAP) courses such as academic writing. However, it is believed that the learning and teaching of these verbs goes far beyond the lists of EAP verbs. This is because knowledge of lexical verbs entails not only the knowledge of grammatical structures, but also the knowledge of semantic and syntactic structures. Therefore, this study aims to investigate how commonly used lexical verbs are used in learner writing in the perspectives of grammatical, semantic and syntactic features of verb-noun collocations. To achieve this, a corpus-based study using WordSmith Tools was employed on a learner corpus of Malay ESL learners to identify most-commonly used lexical verbs. These verbs were further given a linguistic analysis using a phraseological-based approach. The findings revealed that the use of transitive verbs led to several occurrences of verb-noun collocations and that the phraseological patterns of these verbs are bound by both lexical and grammatical patterns. This leads to the conclusion that the teaching of lexical verbs, specifically Verb-Noun collocations in academic writing should not only include the semantic elements, but also the syntactical elements of the verbs. It is then recommended that a lesson on lexical verbs should incorporate the teaching and learning of both lexis and grammar.